Globalizing Cricket Englishness, Empire and Identity - Malcolm, Dominic (Globalizing Sport Studies, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Globalizing Cricket examines the global role of the sport - how it developed and spread around the world. The book explores the origins of cricket in the eighteenth century, its establishment as England's national game in the nineteenth, the successful (Caribbean) and unsuccessful (American) diffusion of cricket as part of the development of the British Empire and its role in structuring contemporary identities amongst and between the English, the British and postcolonial communities. Whilst empirically focused on the sport itself, the book addresses broader issues such as social development, imperialism, race, diaspora and national identities. Tracing the beginnings of cricket as a 'folk game' through to the present, it draws together these different strands to examine the meaning and social significance of the modern game. This book is a must-read for anyone interested in the role of sport in both colonial and post-colonial periods; the history and peculiarities of English national identity; or simply intrigued by the game and its history.